Downregulation of circRNA_100876 Inhibited Progression of NSCLC In Vitro via Targeting miR-636. (7th October 2020) - Song, Jianxiang; Shi, Woda; Gao, Zhengya; Liu, Xingchen; Wang, Wencai
Background: Non-small cell lung carcinoma (NSCLC) is a common malignant tumor with poor prognosis. CircRNA-100876 has been considered to be involved in NSCLC. However, the mechanism by which circRNA_100876 mediated the progression of NSCLC remains unclear. Methods: CCK8 assay and immunofluorescence were used to detect cell proliferation. Flow cytometry and transwell assay were performed to analyze cell apoptosis, migration and invasion, respectively. Verification of possible target for circRNA_100876 and related miR-636 were done using luciferase assay. In addition, western blot was performed to detect the protein expressions in NSCLC cells. Results: Silencing of circRNA_100876 notably inhibited the proliferation of NSCLC cells. Moreover, downregulation of circRNA_100876 significantly induce the apoptosis of NSCLC cells via mediation of apoptosis-related proteins. In addition, silencing of circRNA_100876 significantly inhibited migration and invasion of NSCLC cells. MiR-636 was the downstream target of circRNA_100876. Meanwhile, RET was the direct target of miR-636. Finally, circRNA_100876 shRNA2 notably suppressed the progression of NSCLC through PI3K/Akt signaling. Conclusion: CircRNA_100876 knockdown notably suppressed the progression of NSCLC through regulation of miR-636/RET axis, which may serve as a potential target for treatment of NSCLC.